Design Method of Core-Separated Assembled Buckling Restrained Braces Confined by Two Lightweight Concrete-Infilled Tubes - Boli Zhu; Junyuan Zhao; Yuqing Yang (Applied Sciences, 2023)
This paper introduces a novel type of buckling restrained braces (BRBs) called core-separated assembled BRBs (CSA-BRBs). These braces are comprised of two single BRBs that are confined by lightweight concrete-infilled tubes, which are longitudinally connected by two continuous webs. The CSA-BRBs utilize materials more efficiently by increasing the height of the webs to create a large inner cavity, leading to an economical design. This paper predicts the threshold of the restraint ratio of CSA-BRBs approximately. This is achieved by assuming that the maximum moment resulting from applied loads at mid-height is less than the moment-bearing resistance that is conducted according to the outermost fiber of the external restraining section reading yielding. Elastic-plastic numerical analysis is conducted using FEM with beam elements for CSA-BRBs that are subjected to both monotonic and cyclic axial loads. The load resistance, hysteretic performance, and failure mechanism of CSA-BRBs are investigated by varying their restraining ratios. It is recommended that the restraint ratio threshold of CSA-BRBs under monotonic axial compression is used as a bearing type and the restraint ratio threshold of CSA-BRBs under axially compressive-tensile cyclic loads as an energy-dissipation type. This method provides a complete design for CSA-BRBs.